The Effectiveness of Using “New Big City Adventure Game” in Enhancing Students’ Vocabulary Mastery in Vocational High School Level - Radita, Cindy; Yuniar, Rendhi Fatrisna (English Edu: Journal of English Teaching and Learning, 2022)
The objective of this research is to investigate whether “New Big City Adventure Game” can increase the students’ vocabulary mastery or not. The data were gathered using two kinds of instruments; those are (1) vocabulary tests, (2) questionnaires. The vocabulary tests were pre and post-tests, while the questionnaires were distributed to the students’ of the experimental group and the teacher. The study's findings revealed that “New Big City Adventure Game” successfully enhanced the students’ vocabulary mastery. Besides, it could trigger the students’ motivation to learn English. The result was proven by the gain of the experimental group’s performance after being given treatment by the researcher. In addition, the results of the students and teacher’s questionnaires showed positive responses towards the treatment given.